Designing an Ergonomic-Based Work Facility of Dough Stirrer for Kerupuk Cipir Using Rapid Entire Body Assesment (REBA) Analysis to Reduce Muskuloskeletal Complaints and Increase Productivity - Tri Budiyanto; Fakhri Agus Setiyoso (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2021)
Abstract. The small and medium-sized enterprises (UKM) of Kerupuk Cipir are the home industries which produce kerupuk cipir. During the making process, there were still many phases which were done manually using a simple work facility. During the dough stirring phase, the workers used a bending work posture (unergonomic) which caused musculoskeletal complaints and various problems toward the workers. Therefore, a research was conducted by applying rapid entire body assesment (REBA) analysis to decrease musculoskeletal complaints and increase productivity. The research was conducted experimentally at UKM Kerupuk Cipir in Binangun Village, Karangpucung District, Cilacap Regency by using the treatment by subject design. There were two treatments given toward the sample: stirring the dough using the former work facility and stirring the dough using the improved work facility through ergonomic approach. The musculoskeletal complaints were measured using Nordic Body Map questionnaire. The data were analyzed using descriptive and inferential statistics. The results showed a decrease on REBA score from 11 on level 4 which was in the category of high risk into score of 4 on level 2 which was in the category of quite high when the handle position is on the upper side, score of 5 when the handle position is on the front side, and score of 7 when the handle position is on the lower side. The workers’ complaints of severe pain on 9 body parts and pain on 6 body parts were decreased into mild pain on 7 body parts and no pain on 20 other body parts. Work productivity increased into 89.62%.